Promises Undone: How Committed Pledges Impact Donations to Charity - Toke R. Fosgaard; Adriaan R. Soetevent (Tinbergen Institute, 2018)
The declining use of cash in society urges charities to experiment with digital payment instruments in their off-line fund raising activities. Cash and card payments differ in that the latter do not require individuals to donate at the time of the ask, disconnecting the decision to give from the act of giving. Evidence shows that people who say they will give mostly do not follow through. Our theory shows that having people to formally state the intended amount may alleviate this problem. We report on a field experiment the results of which show that donors who have pledged an amount are indeed more likely to follow through. The firmer the pledge, the more closely the amount donated matches the amount that was pledged. 45% of all participants however refuses to pledge. This proves that donors value flexibility over commitment in intertemporal charitable giving.
Keywords: C93; D64; D91; H41; 330; Charitable fundraising; Field experiment; Image motivation